PENGARUH FAKTOR INTERNAL DAN EKSTERNAL BANK SYARIAH TERHADAP KEPUTUSAN INVESTASI SURAT BERHARGA BANK SYARIAH - Izzadin Nur Muhammad; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Investments of securities performed by Islamic banks in addition to a liquidity instrument in the bank that is as an investment instrument for banks to obtain operating income other than the channeling of funds through financing to customers. The Bank's securities investment is influenced by external and internal factors within the bank. External factors are factors that occur outside the bank, external factors can not be controlled by the management of sharia banks. Internal factors are factors that occur due to decisions and phenomena within the internal bank, internal factors can be controlled by banks through managerial processes. External factors faced by banks such as economic and monetary conditions such as inflation and interest rates, money market conditions (exchange rate), customer character, regulations and others. Internal factors rely heavily on bank management in managing every liquid instrument within the sharia bank itself, such as asset and liability management.Keywords: Sharia Bank, Investment, SBSN, Liquid InstrumentsREFERENCESAl-Qur’an dan Terjemahannya.Airlangga, Universtity. 2009. Pedoman Penulisan Pembimbingan dan Ujian Skripsi. Surabaya : Airlangga University Press.Ajija, Shochrul R dkk. 2011. Cara Cerdas Menguasai EViews. Jakarta : Salemba Empat.Alma, Buchari & Donni Juni Priansa. 2009. Manajemen Bisnis Syariah. Bandung : Alfabeta.Antonio, Muhammad Syafi’i. 2001. Bank Syariah Dari Teori ke Praktik. Jakarta: Gema Insani.Arifin, Zainul. 2003. Dasar-Dasar Manajemen Bank Syariah. Jakarta : AlvaBet.___________. 2009. Dasar-Dasar Manajemen Bank Syariah. Ciputat-. Tanggerang: Azkia.Ascarya, 2008. Akad dan Produk Bank Syariah, Jakarta : PT.Raja Grafindo. Persada.Boediono. 1985. Teori Pertumbuhan Ekonomi. Yogyakarta : Penerbit BPFE. ________.  2005. Ekonomi Moneter Edisi 3. Yogyakarta.: BPFE.Dendawijaya, Lukman. 2005. Manajemen Perbankan. Edisi Kedua. Bogor : Ghalia IndonesiaHasan, Nurul Ichsan. 2014. Pengelolaan Likuiditas Bank Syariah. Al-Iqtishad: Journal of Islamic Economics 2014.Huda, Nurul  dan Heykal, Mohamad .2010.  Lembaga Keuangan Islam: Tinjauan Teoritis dan. Praktis. Jakarta: Kencana.Ismal, Rifki. 2010.  The management of liquidity risk in Islamic Banks: the case of indonesia , Durham University : Doctoral dissertation._________. 2013. Islamic Banking in Indonsia: New Perspectives on Monetary and Financial Issues. Singapore: John Wiley. Kasmir .2012. Analisis Laporan Keuangan.Jakarta: Salemba Empat.Mankiw, Gregory. 2005. Teori Makroekonomi. Jakarta: Erlangga.Widjajono Moestadjab. 1995.  Asset Liability Management (ALMA). Surabaya:    BP-IPIMuhammad. 2005. Manajemen Perbankan Syariah. Yogyakarta: UPP STIM YKPN.__________. 2006. Bank Syariah Analisis Kekuatan, Peluang, Kelemahan dan Ancaman. Yogyakarta: EKONISIA________. 2011. Manajemen Bank Syariah. Yogyakarta: UPP STIM YKP________. 2015. Manajemen Dana Bank Syariah. Jakarta:PT RajaGrafindo PersadaMuljawan, Dadang. dkk. 2014. Penggunaan Sukuk IILM Sebagai Instrumen Investasi dan Likuiditas Perbankan Syariah.Working Paper 7 Bank Indonesia Desember 2014.Rivai, Veitzhal dkk. 2012. Principle of Islamic Finance ( Dasar-DasarKeuangan Islam ). Yogyakarta : BPFE.Soemitra,Andri . 2009. Bank dan Lembaga Keuangan Syariah. Jakarta: Kencana. Tandelilin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi. Edisi pertama. Yogyakarta : Kanisius. Taswan. 2010. Manajemen Perbankan Konsep, Teknik, dan Aplikasi. Edisi. Kedua. Yogyakarta: UPP STIM YKPN.Umar, Azwar. 2014. Pengaruh Penerbitan Sukuk Negara Sebagai Pembiayaan Defisit Fiskal dan Kondisi Ekonomi Makro Terhadap Perkembangan Perbankan Syariah di Indonesia. Jurnal of Info Artha Sekolah Tinggi Akuntansi Negara (STAN). II. 1-21.Undang-Undang No.21 tahun 2008www.academia.edu/25443636/MANAJEMEN_DANA_BANK_SYARIAHdiaksespada 25 Februari 2018www.bi.go.iddiaksespada 25 Februari 2018www.ojk.go.iddiaksespada 24 Februari 2018https://www.brisyariah.co.id/files/reports/annual_2012.pdfdiaksespada 24 Februari 2018